A Korean boy with atypical X-linked adrenoleukodystrophy confirmed by an unpublished mutation of - Hye Jeong Jwa; Keon Su Lee; Gu Hwan Kim; Han Wook Yoo; Han Hyuk Lim (Korean Pediatric Society, 2014)
X-linked adrenoleukodystrophy (X-ALD) is a rare peroxisomal disorder, that is rapidly progressive, neurodegenerative, and recessive, and characteristically primary affects the central nervous system white matter and the adrenal cortex. X-ALD is diagnosed basaed on clinical, radiological, and serological parameters, including elevated plasma levels of very long chain fatty acids (VLCFA), such as C24:0 and C26:0, and high C24:0/C22:0 and C26:0/C22:0 ratios. These tests are complemented with genetic analyses. A 7.5-year-old boy was admitted to Department of Pediatrics, Chungnam National University Hospital with progressive weakness of the bilateral lower extremities. Brain magnetic resonance imaging confirmed clinically suspected ALD. A low dose adrenocorticotropic hormone stimulation test revealed parital adrenal insufficiency. His fasting plasma levels of VLCFA showed that his C24:0/C22:0 and C26:0/C22:0 ratios were significantly elevated to 1.609 (normal, 0-1.390) and 0.075 (normal, 0-0.023), respectively. Genomic DNA was extracted from peripheral whole blood samples collected from the patient and his family. All exons of ABCD1 gene were amplified by polymerase chain reaction (PCR) using specific primers. Amplified PCR products were sequenced using the same primer pairs according to the manufacturer's instructions. We identified a missense mutation (p.Arg163Leu) in the ABCD1 gene of the proband caused by the nucleotide change 488G>T in exon 1. His asymptomatic mother carried the same mutation. We have reported an unpublished mutation in the ABCD1 gene in a patient with X-ALD, who showed increased ratio of C24:0/C22:0 and C26:0/C22:0, despite a normal VLCFA concentrations.